اللوحة الجدارية في العمارة الحديثة (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2019)
تطور مفهوم اللوحة الجدارية عبر التاريخ,و مدارسها, أنواعها,و خاماتها,ووظيفتها كالتالي: • · ظهور الرسومات الجدارية في مصر القديمة وبلاد ما بين النهرين على شكل روليفات غائرة ملونة,استخدمت فيها الأصباغ,و البودرة الملونة • · في المرحلة الكلاسيكية الإغريقية الرومانية,تغير الذوق الجمالي من فترة لأخرى,و استخدم الفنانون الرومان و الإغريق مهاراتهم الفائقة في خدمة التفاصيل الدقيقة . • · المرحلة البيزنطية: وفيها سعى الفنانون للوصول إلى حالة الكمال في لوحة الموزاييك (سمالتا) .• · المرحلة الإسلامية : وفيها وصلت الجداريات إلى الرقي بتشكل التجمعات العمرانية المتكاملة,و ظهور التأثيرات الهيلينية,و البيزنطية,و الفارسية فيها, ومن أفضل الأمثلة موزاييك الجامع الأموي, فريسك قصر الحير الغربي بالملامح المحلية. وظهرت الشخوص في المرحلة العباسية, تطورت الزخرفة الهندسية, النباتية,و الخط العربي فيها • · المرحلة الغوطية (غوتيكا): حيث كانت الكنيسة هي من أهم الأوابد المعمارية,و وضعت في فتحاتها المعمارية الكبيرة,و نوافذها ألواح من الزجاج الملون .• · مرحلة عصر النهضة: وفي هذه المرحلة,ظهرت تقنيات جدارية هامة مثل (السيغرافيتو) • · مرحلة ما بعد عصر النهضة:ففي منتصف القرن 17 بدأ مفهوم التزيين بتغيير من ميزات الشخوص بالألوان الكتيمة,و الضوء غير الطبيعي المجسم الواقعي, الأكاديمي في الباروكو إلى أسلوب أقل تعقيداً للفنانين .• · و في مرحلة الروكوكو في ثلاثينات,و أربعينات القرن 18 في فرنسا وجوارها, أصبحت اللوحة الجدارية,تغطي كامل الأسقف,و فيها المناظر,و الميثولوجيا,و مشاهد الحياة الأرستقراطية على القماش,و سميت بالجداريات الديكورية • · المراحل الحديثة مع نهايات القرن 19 ,وبدايات العشرين,تغير التذوق الفني في فن الديكور مع أعمال غوستاف,و غاودي,و كليمنت,و هوندرفاسي وظهرت الحركة الديناميكية للموزاييك في أعمال ريفيرا . وما زالت الأعمال الجدارية تجد لنفسها المكانة المناسبة في التصميم المعماري الداخلي,و الخارجي ثم أصبحت مستقلة فراغياً . The development of the Monumental Painting concept through history :its schools, kinds, materials and function as follows : lThe emergence of Monumental drowings in ancient Egypt and the Mesopotamia : in the shape of frieze that was painted by using pigments and powder . l Mural Painting in the Classical, Greek and Roman Periods: The aesthetic taste has changed from one period to another and the Roman and Greek artists used their supreme skills in the service of minute details . l The Monumental Painting in the Byzantine Period:In this period the artists sought to reach for a state of supremeness in the Mosaics paintings (smalt) . l The Islamic Period: In this period Monumental Painting was highly developed by the formation of integrated Urban complexes and the appearance of Hellenistic, Byzantine and Persian influences, of which the Mosaics of the Umayyad Mosque and the Fresco of Al-Heer western palace are better examples in local characteristics. In the Abassid period, painting of persons appeared, geometrical and plant ornamentation developed including Arabic fonts l Monumental Painting in the Gothic Period: In this period the church was considered the most important of architectural elements. Panels of Stained glass have been put on windows and large openings . l Monumental Painting in the Renaissance Period: In this period very important Mural techniques appeared such as ( Sagrafito-scratch work ) . lThe Post Renaissance Period: In the middle of the 17th century the concept of ornamentation started to change. It was changed from characterizing persons in deep colors, unnatural and enlarged light, acadimic and realistic in Baroco to a less restreitive technique for artists. In the Rococo period, in the thirtieth and fortieth of the 18th century, Mural Painting covered roofs completely through which scenery, methodology and aristocratic lifestyle have been painted on fabrics and were called the decorative paintings . l The Modern Periods: At the end of the 19th century and the beginning of the 20th century the artistic taste in decoration changed with the work of Gostav, Klimt, and Antony Gaudi. The dynamic movement of Mosaics appeared in the works of Revera. However, Mural works still find for themselves the appropriate status within the interior and exterior design, which thereafter have become spatially independent .